Optical Solutions of Schrödinger Equation Using Extended Sinh–Gordon Equation Expansion Method - Irshad, Amna; Ahmed, Naveed; Khan, Umar; Mohyud-Din, Syed Tauseef; Khan, Ilyas; Sherif, El-Sayed M. (Frontiers in Physics, 2020)
In this paper, we investigated the non-linear Schrödinger equation (NLS) to extract optical soliton solutions by implementing the extended Sinh–Gordon equation expansion method (ShGEEM). Optical soliton solutions included bright, dark, combined bright-dark, singular soliton combined singular soliton solutions, and singular periodic wave solutions. Our new results have been compared to these in the literature. Also, graphical analysis was presented with 3D and contour graphs to understand the physics of obtained solutions.